2005
DOI: 10.1007/s00280-005-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Curcuminoids purified from turmeric powder modulate the function of human multidrug resistance protein 1 (ABCC1)

Abstract: Multidrug resistance is a major cause of chemotherapy failure in cancer patients. One of the resistance mechanisms is the overexpression of drug efflux pumps such as P-glycoprotein and multidrug resistance protein 1 (MRP1, (ABCC1)). In this study, curcumin mixture and three major curcuminoids purified from turmeric (curcumin I, II, and III) were tested for their ability to modulate the function of MRP1 using HEK293 cells stably transfected with MRP1-pcDNA3.1 and pcDNA3.1 vector alone. The IC(50) of curcuminoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 24 publications
3
54
0
Order By: Relevance
“…Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents. 28,29 However, its clinical application is severely restricted due to its low water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that Cur can significantly inhibit the proliferation of glioma cells by downregulating multidrug resistance proteins that cause the efflux of many chemotherapeutic agents. 28,29 However, its clinical application is severely restricted due to its low water solubility.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that curcuminoids are inhibitors of the ABC transporters, ABCB1 (25,26) and ABCC1 (27), which are known to play a major role in the development of MDR in cancer cells. In this study, purified curcuminoids were tested for their interaction with ABCG2.…”
Section: Discussionmentioning
confidence: 99%
“…NF-ÎșB regulates the expression of genes involved in the suppression of the apoptotic response, and is responsible for tumor cell survival (6). Additionally, Cur is also known to downregulate the intracellular levels of three major ABC drug transporters, P-gp, MDR-associated protein 1 (MRP1) and ABCG2, which are important in MDR (7)(8)(9). In spite of these various promising therapeutic applications of Cur, its therapeutic efficacy is limited due to its markedly poor water solubility, and consequently, remarkably low systemic concentrations are achieved when Cur is consumed orally (4).…”
Section: Introductionmentioning
confidence: 99%